Styvbarnen i folkhemmet? Utanförskap i svenska barndomsskildringar - Żmuda-Trzebiatowska, Magdalena (Folia Scandinavica Posnaniensia, 2012)
The subject of the article is the experience of social exclusion present in five contemporary novels on childhood and adolescence spent in the Swedish folkhem, by Jonas Gardell, Lena Andersson, Mikael Niemi, Torbjörn Flygt and Susanna Alakoski. In the first part of the article I am discussing social exclusion as a term used in the debate about the Swedish welfare-state in crisis. The second part is an analysis of the literary texts, using a sociological perspective. I am focusing there on portraits of the children that are main characters in the novels, the children whose personal identity is being shaped in the shadow of the collective dream of a perfect society. Asking a question about the specifically Swedish character of those children’s sense of exclusion, I am referring to the words of the social democratic leader Per Albin Hansson, who in his speech of 1928, presented a vision of Sweden as a happy and fair common home (folkhem), in which there is no place for either favored citizens (“darlings”), or for second-class citizens (“stepchildren”).